Identitätskrise eines Schweins: Eine motivanalytische Untersuchung von Ps 80,14a - Bursztyn, Michał (Revue biblique, 2021)
The pig, commonly interpreted as a wild boar, harming psalm 80’s vine transplanted from Egypt, has an uncertain identity. Some textual difficulties relating to this image deserve further study in order to clarify the most probable meaning. A comparison of the short phrase with a related motif in the Iliad depicts that a damaging boar is not singular to psalm 80. Furthermore, the motif’s purpose is to picture warlike destruction. Therefore it is not necessary to interpret the boar as a metaphor for political force, as scholars have proposed repeatedly.